A new minute Andean Pristimantis (Anura: Strabomantidae) from Venezuela - Barrio-Amorós, César (2012)
A new species of Pristimantis is described from the Venezuelan Andes. The new species is the smallest in its genus known in Venezuela and belongs to the Pristimantis unistrigatus Group. It differs from the rest of Venezuelan Andean congeners in body size (mean male SVL < 21.3 mm, female SVL < 26.3 mm), expanded discs on fingers and toes, absence of dorsolateral folds, and a distinctive call consisting in 2-5 cricket-like short notes. The new species inhabits the southwestern part of the Cordillera de Mérida in Venezuela and the Venezuelan side of the Cordillera Oriental de Colombia, and could be present on the Colombian portion of the cordillera as well. © 2012 Departamento de Ciências Biológicas.